Pengaruh Literasi Keuangan dan Sikap Keuangan Terhadap Pengelolaan Keuangan yang Dimoderasi Gender pada Mahasiswa Manajemen UBP Karawang - Renaldi, Aldi; Ujang Suherman; Rengga Madya Pranata (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted to see the influence of financial literacy and financial attitudes on the financial management of UBP Karawang management students moderated by gender. This type of research is quantitative research where there is theory testing. The population in this study were 2020-2021 UBP Karawang management students totaling 897 students. The sample was 109 people representing UBP management students. The method used is purposive sampling. Data was collected by distributing questionnaires via Gform. The analysis technique used is moderated regression analysis. The results of this research are that financial literacy has a positive and significant effect on financial management. Financial attitudes can significantly influence the financial management of UBP Karawang management students. Financial literacy and financial attitudes simultaneously influence the financial management of UBP Karawang management students. Gender cannot moderate the influence of financial literacy towards the financial management of UBP Karawang management students, gender is unable to moderate the influence of financial attitudes on the financial management of UBP Karawang management students.